The role of mobile handheld lung ultrasound in the diagnosis and monitoring of C0VID-19 atypical pneumonia - Omeroglu, Sabri Alp; Aybar, Mustafa Devran; Kolca, Cilem (Global Journal of Medical and Clinical Case Reports, 2021)
Background: Our aim is to present the importance of mobile Handheld Lung Ultrasound (HLUS) in COVID-19 patients at the bedside, which is a pre-screening tool with high diagnostic value that can provide triage of symptomatic patients at home (pre-hospital), emergency services, Intensive Care Units (ICU). In this context, the current role and importance of HLUS at the bedside in COVID-19 pneumonia has been summarized. Method: We searched pubmed with key words; COVID-19 pneumonia, Lung Ultrasound (LUS), handheld ultrasound and reached 2428 articles with full texts. All abstracts were searched and 470 systematic review and meta-analysis determined. Only 10 articles were directly related to COVID-19 pneumonia and HLUS. These articles were interpreted to determine the role of HLUS at the bedside in COVID-19 pneumonia. Results: Although not specific for COVID-19, Ultrasonography (US) findings of peripheral interstitial viral pneumonias due to COVID-19 lung involvement are very characteristic. The use of HLUS in COVID-19 atypical pneumonia is of critical importance due to its high diagnostic value in diagnosis and follow-up. It was shown that the sensitivity and specificity of bedside LUS in the diagnosis of atypical pneumonia were high enough to include in radiologic algorithm. Conclusions: Handheld pocket-sized US devices are cheap, easy to handle and equivalent to standard scanners for non-invasive assessment of severity and dynamic observation of lung lesions in COVID-19 patients with pneumonia. So it has become of great importance to make a useful and simple radiological algorithmic approach that includes bedside HLUS in the diagnosis and follow-up of COVID-19 pneumonia patients.